Protein and Virus Encapsulation for Delivery. - Zhou, Chensheng. (2017)
Abstract: This thesis presents encapsulation techniques for biomedical applications, including enzyme encapsulation and immobilization for correcting enzyme deficiency, and vaccinia virus formulation for vaccinate wild animals. The first chapter describes a formulation strategy that protects therapeutic enzymes by encapsulation and immobilization them into a hydrogel. Enzyme deficiency related genetic disorder diseases usually develop mildly but can cause vital damage when left untreated. Enzyme replacement therapy, which artificially supplies a replacement of the defected enzyme, was first demonstrated in 1970s.[1] It is an effective, cost effective and safe way to control these diseases. In this research, we are figuring out a way to make the therapeutic enzyme more compatible with in vivo environment, so they can last longer. Using enzyme encapsulation and immobilization strategies, the enzyme activity can be preserved for longer time as well as escaping from immune response. The second chapter is about engineering a bait-vaccine oral delivery system, for controlling Lyme disease. Vaccinate the bacteria reservoir animal is one of the approaches to control this infectious disease. We were developing a formulation procedure for the vaccinia virus and antigen protein enteric delivery. Since the vaccine will be distributed to the wild, there is additional concern about avoiding random infections. We have adapted and invented several methods including wet formulation, semi-dry formulation and dry formulation. Our goal was to engineer a reliable enteric formulation for vaccinate wild animals.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Biomedical Engineering.; Advisors: Qiaobing Xu, and Linden Hu.; Committee: Qiaobing Xu, Linden Hu, and Lauren Black.; Keywords: Biomedical engineering, and Pharmaceutical sciences.